On the Be and Ae Stars in NGC 6611 - Herbig, G. H.; Dahm, Scott E. (Publications of the Astronomical Society of the Pacific, 2001)
The young cluster NGC 6611 is of interest because it has been believed to contain an unusually large number of Be and Ae stars. The cluster is embedded in a very bright Hiiregion, so that proper subtraction of that background on slit or multiobject fiber‐fed spectra is important. If stellar line emission is present in blue‐violet Balmer lines, it should be more prominent at Hα. We have examined some 40 of these cluster stars on Hα slitless spectrograms, which are not subject to such contamination, and were able to confirm the presence of Hα emission above the continuum level in only four. About 25 much fainter Hα emitters were found in the cluster; these are probably the brightest members of a low‐mass T Tauri population. None are convincingly associated with the famous elephant‐trunk structures seen in projection against the Hiiregion.